Economic research at central banks: Are central banks interested in the history of economic thought? - Ivo Maes (National Bank of Belgium, 2022)
With central banks becoming monetary authorities, research departments have become a core element of a modern central bank. Crucial elements of a central bank research department are contributing to monetary policymaking and sustaining a dialogue with the academic community. The importance of historical research (and central banks do not really make a difference between economic history and the history of economic thought) varies a lot. The historical curiosity of influential central bankers and the commemoration of anniversaries are important factors hereby. Historical research can allow central banks to take more distance and can help to avoid a "this time is different" view.
Keywords: E42; E58; G28; N10; 330; central banking; economic research; economic history; history of thought